When Illiberals Govern: Educational and Cultural Policies in Hungary and Poland - Péter Radó; Bálint Mikola (Politics and Governance, 2025)
Illiberal governments have been widely associated with democratic backsliding, the erosion of the rule of law, and executive aggrandisement. However, their impact on the various domains of knowledge production has not received enough scholarly attention. Through what policies do illiberal actors ensure the reproduction of their narratives? Do illiberal political leaders see education and culture as ideological vehicles, or do they consider them as arenas for power distribution? The article addresses these questions through the educational and cultural policy changes in two crucial cases of illiberals in power: post-2010 Hungary and 2015–2023 Poland. The article distinguishes between overt and hidden policy agendas, i.e., initiatives and aspirations that are driven by values and social or economic goals vs. policies serving purposes that cannot be openly represented. Through the analysis of legislative changes, party programs, and party discourse, complemented with semi-structured expert interviews, the study finds that despite sharing similar policy agendas, Fidesz and PiS considerably differ in the extent to which they transformed educational and cultural policies during their reign. While the main feature of educational and cultural policies in Hungary has been radical political power concentration, these policies in Poland rather served the ideological goals of the illiberal culture war. The article concludes that these differences were caused by the latitude afforded to these parties by their respective legislative majorities, indicating that whether illiberals have a supermajority in parliament influences the extent to which they can abuse their power.